Three β-Glucuronosyltransferase Genes Involved in Arabinogalactan Biosynthesis Function in Arabidopsis Growth and Development - Oyeyemi O. Ajayi; Michael A. Held; Allan M. Showalter (Plants, 2021)
Arabinogalactan proteins (AGPs) contain arabinogalactan (AG) polysaccharides that are biologically relevant to plant growth processes. Here, the biochemical and physiological roles of three Golgi localized β-glucuronosyltransferase genes (GLCAT14A, GLCAT14B and GLCAT14C) in Arabidopsis thaliana, responsible for the addition of glucuronic acid to AG chains, were further investigated using single, double and triple glcat14 mutant plants. These proteins were localized to the Golgi apparatus when transiently expressed in Nicotiana benthamiana. Sugar analysis of AGP extracts from Arabidopsis stem, leaf and siliques showed a consistent reduction in glucuronic acid in glcat14 mutants relative to wild type, with concomitant effects resulting in tissue-specific alterations, especially in arabinose and galactose sugars. Although we observed defects in trichome branching in glca14a/b and glca14a/b/c mutants, scanning electron microscope analysis/energy dispersive microanalysis (SEM/EDX) showed no difference in the calcium content of trichomes in these mutants relative to wild type. Immunoblot analyses of the stem and leaf showed a reduction in AGPs as detected with the LM2 antibody in glcat14a/b and glcat14a/b/c mutants relative to wild type. The current work exemplifies the possibility of conducting structure-function assessment of cell wall biosynthetic genes to identify their physiological roles in plant growth and development.